Efficient environment-friendly novel curing agent and preparation method thereof
By using low-carbon industrial solid waste gel powder, aluminate and other materials in the sludge curing agent, and adding lignocellulose and nano silicon carbide, a multi-layer structure is formed, the problem of insufficient strength of sludge curing agent in seawater environment is solved, and an efficient and environmentally friendly sludge curing effect is achieved.
Patent Information
- Application Number
- CN202510089592.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, sludge curing agents are difficult to solidify in seawater environments, which affects the curing strength, resulting in the construction of engineering in coastal areas that requires cover construction and construction of drainage facilities, which is time-consuming and labor-intensive.
Provide a new high-efficiency and environmentally friendly curing agent, which includes low-carbon industrial solid waste gel powder, sulfur aluminate cement, silicate cement, fly ash, ore powder, modified polymer, desulfurization dihydrate gypsum, grinding aid, cement premature strength agent, water reducing agent powder and cement coagulation promoter. The curing agent is used as a curing gelling material through aluminate, sulfaluminate, silicate, etc., and lignocellulose and nano-silicon carbide are added to form a multi-layer structure to improve compactness and strength.
This new curing agent can still maintain high strength in seawater environment, cure quickly, have good dispersion resistance, is green and low-carbon, and is suitable for the curing and stabilization of various soils and silts. It can achieve high compressive strength and water stability under small doses, and has good anti-freeze and thawing effect.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building engineering materials, and in particular to a new type of high-efficiency and environmentally friendly curing agent and a preparation method thereof. Background Art
[0002] Silt is a honeycomb structure formed by the deposition of fine particles such as clay minerals in a static or slow-flowing water environment under the action of inter-particle electrostatic force and molecular gravity, and through biochemical action. Silt has a high natural water content and a large porosity; it has high compressibility, low shear strength, poor water permeability, thixotropy and is in a flowing state, and cannot be directly used for engineering;
[0003] Since there are many oceans, rivers and lakes in my country, a large amount of silt is produced. The soft soil foundation formed by silt dumping is very weak and not easy to use, which damages the ecological environment. In addition, the silt has a complex composition. In addition to a large amount of water, it also contains a variety of heavy metals, organic pollutants, pathogenic microorganisms, parasite eggs and other harmful substances. It is large in size, easy to rot and stink, and easy to pollute the soil and water. Therefore, if it is not treated harmlessly, it will cause serious secondary pollution to the environment.
[0004] In-situ solidification treatment technology is a method of using a solidifying agent to solidify soft soil, silty soil and other soils with poor bearing capacity in situ, so that the soil reaches a certain strength, thereby meeting the natural bearing capacity and heavy equipment load requirements, and at the same time forming a plate to achieve the purpose of foundation treatment;
[0005] However, in coastal areas, the chloride ions in seawater are highly corrosive, which will seriously affect the strength of the solidification under the influence of seawater. The sludge solidifiers on the market are currently unable to solidify in a seawater environment. In order to ensure that the strength will not be affected by seawater, the construction site will be sealed and drainage facilities will be built, which is time-consuming and labor-intensive. Summary of the invention
[0006] The embodiments of the present application provide a solution to the technical problem in the prior art that the performance of the curing agent in the river dredging and sludge solidification technology is difficult to meet the engineering needs, and realizes that the curing agent is suitable for the solidification and stabilization of various types of soil and sludge.
[0007] The present application provides a novel high-efficiency and environmentally friendly curing agent, the composition of which specifically includes the following components in parts by weight:
[0008] Base material cementitious materials: low-carbon industrial solid waste cementitious powder: 35-45 parts; sulphoaluminate cement: 10-15 parts; silicate cement: 10-20 parts; fly ash: 8-10 parts; mineral powder: 10-20 parts;
[0009] Modified polymer: redispersible latex powder: 0.25-0.35 parts; polyvinyl alcohol: 0.15-0.25 parts; cellulose ether: 0.2-0.3 parts; xanthan gum: 0.2-0.3 parts;
[0010] Setting time regulator: desulfurized dihydrate gypsum: 5-8 parts;
[0011] Additives: grinding aid 0.1-0.15 parts; cement early strength agent 0.5-1 parts; water reducing agent powder 0.015-0.020 parts; cement accelerator and curing agent 0.6-1 parts.
[0012] Furthermore, the low-carbon industrial solid waste gelled powder is:
[0013] The industrial solid waste with hydration activity is ground to prepare low-carbon active gel powder, specifically: the powder is ground into a specific surface area of 900-1000cm by a grinding aid. 2 / g of high-activity gelling material.
[0014] Furthermore, the silicate cement uses the new national standard GB175 ordinary silicate cement P.O42.5, with a specific surface area of 360-420m 2 / kg; sulphoaluminate cement is fast-hardening composite sulphoaluminate cement 42.5, with a specific surface area of 360-400m 2 / kg; fly ash is the first-grade ash from power plants; mineral powder is S95 mineral powder.
[0015] Furthermore, the ash content of the redispersible latex powder is 12-18%; the polyvinyl alcohol is PVA2488; the cellulose ether is hydroxypropyl cellulose ether HPMC with a molecular weight of 150,000-200,000; and the molecular weight of the xanthan gum powder is 800,000-1,000,000.
[0016] Furthermore, the early strength agent is sodium sulfate with a sodium sulfate content greater than 98%; the water reducing agent is a polycarboxylic acid high-performance water reducing agent; and the cement coagulation and curing agent is aluminum sulfate.
[0017] Furthermore, the low-carbon industrial solid waste gelled powder also contains 0.5-1.5 parts of wood cellulose and 0.1-0.3 parts of nano silicon carbide.
[0018] Furthermore, the length of the wood cellulose is 20-50 μm, the diameter is 1-10 μm, and the particle size of the nano-silicon carbide is 100-200 nm.
[0019] Furthermore, nano-silicon carbide also includes two specifications, including large particles: particle size 300-500nm; small particles: particle size 1-100nm.
[0020] Furthermore, the mass ratio of large particles: small particles is (1-9): (1-9).
[0021] The preparation method of the above-mentioned high-efficiency and environmentally friendly new curing agent is obtained, and the specific steps are: adding the base material gelling material into a dry mixing mixer in sequence, then adding the cement early strength agent, stirring for 2 minutes, and then adding the modified polymer, and continuing to stir for 3 minutes; then adding other additives except the cement early strength agent, continuing to stir for 7 minutes, and discharging the material to obtain the curing agent.
[0022] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:
[0023] First, by using aluminates, sulphoaluminates, silicates and the like as curing cementitious materials and adding additives that stimulate the activity of cementitious materials, a new type of environmentally friendly curing agent with fast curing, good anti-dispersion, and green and low-carbon properties is prepared. It can be used for the curing and stabilization of various types of soils and silts. When the curing agent dosage is small, the cured soil specimens formed by pressing have an unconfined compressive strength of 2 hours, fast strength development, good water stability, and good anti-freeze-thaw effect.
[0024] Secondly, by adding cellulose, the dispersibility and workability of the gelling powder are improved, making the curing agent easier to mix and evenly distribute during the preparation and use process. Cellulose has strong water absorption and contains a large number of hydroxyl groups (-OH) on its molecular chain. These hydroxyl groups can form hydrogen bonds with water molecules, so that water molecules are adsorbed on the cellulose molecular chain. This characteristic greatly promotes the contact between cement and other gelling materials and water, and accelerates the initial stage of the hydration reaction; and cellulose can effectively increase the interfacial adhesion between organic materials and inorganic materials, can effectively retain water and inhibit cracking.
[0025] Third, the combination of large and small particles can not only form a multi-level structure in the curing agent to improve density and strength; it can also provide an origin for the hydration reaction, so that the hydration reaction occurs more around the small particles, and the small particles are more distributed on the surface of the large particles or in the gaps they produce, making the large particles the center of the hydration reaction, producing a structural ladder of outer layer gel-middle layer small particles-inner layer large particles, which greatly increases its stability and further improves the pressure-bearing capacity after curing.
[0026] Fourth, large particles are more suitable for application scenarios such as rapid sedimentation and dehydration, high-strength foundation treatment, rapid construction and backfilling; small particles are more suitable for scenarios such as fine filtration and adsorption, ecological restoration and environmental protection, and improving material uniformity and toughness. DETAILED DESCRIPTION
[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.
[0028] Embodiment 1: The present application provides a novel high-efficiency and environmentally friendly curing agent, the composition of which specifically includes the following components in parts by weight:
[0029] Base material cementitious materials: low-carbon industrial solid waste cementitious powder: 35-45 parts; sulphoaluminate cement: 10-15 parts; silicate cement: 10-20 parts; fly ash: 8-10 parts; mineral powder: 10-20 parts;
[0030] Among them, low-carbon industrial solid waste gelled powder is:
[0031] The industrial solid waste with hydration activity (activated coal gangue, fly ash, mineral powder) is ground to prepare low-carbon active gelled powder, specifically: the powder is ground into a specific surface area of 900-1000cm by a grinding aid. 2 / g of high-activity gelling material;
[0032] The silicate cement uses the new national standard GB175 ordinary silicate cement P.O42.5, with a specific surface area of 360-420m 2 / kg; sulphoaluminate cement is fast-hardening composite sulphoaluminate cement 42.5, with a specific surface area of 360-400m 2 / kg; fly ash is the first-grade ash from power plants; mineral powder is S95 mineral powder;
[0033] Modified polymer: redispersible latex powder: 0.25-0.35 parts; polyvinyl alcohol: 0.15-0.25 parts; cellulose ether: 0.2-0.3 parts; xanthan gum: 0.2-0.3 parts;
[0034] Among them, the ash content of the redispersible latex powder is 12-18%; the polyvinyl alcohol is PVA2488; the cellulose ether is hydroxypropyl cellulose ether HPMC (molecular weight 150,000-200,000); the molecular weight of the xanthan gum powder is 800,000-1,000,000;
[0035] Setting time regulator: desulfurized dihydrate gypsum: 5-8 parts;
[0036] Additives: grinding aid 0.1-0.15 parts; cement early strength agent 0.5-1 parts; water reducing agent powder 0.015-0.020 parts; cement accelerator curing agent 0.6-1 parts;
[0037] Among them, the early strength agent is sodium sulfate with a sodium sulfate content greater than 98%; the water reducer is a polycarboxylic acid high-performance water reducer (water reduction rate greater than or equal to 35%); and the cement coagulation and curing agent is aluminum sulfate.
[0038] The preparation method of the above-mentioned curing agent is: add the base material cementitious material into a dry mixing mixer in sequence, then add the cement early strength agent, stir for 2 minutes, then add the modified polymer, and continue stirring for 3 minutes; then add other additives except the cement early strength agent, continue stirring for 7 minutes, and discharge the material to obtain the curing agent.
[0039] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0040] By using aluminate, sulphoaluminate, silicate and the like as curing cementitious materials and adding additives to stimulate the activity of cementitious materials, a new type of environmentally friendly curing agent with fast curing, good anti-dispersion, and green and low carbon properties is prepared. It can be applied to the curing and stabilization of various types of soil and silt. When the curing agent dosage is small, the cured soil specimens formed by pressing have an unconfined compressive strength of 2 hours, fast strength development, good water stability, and good anti-freeze-thaw effect.
[0041] By using low-carbon industrial solid waste gelling powder (such as activated coal gangue, fly ash, mineral powder, etc.), the resource utilization of industrial waste is realized, waste discharge is reduced, and environmental pollution is reduced; the selected additives and modified polymers are environmentally friendly materials, which further improve the environmental performance of the curing agent;
[0042] The addition of modified polymers improves the bonding force and crack resistance of the curing agent, making the cured structure more stable; and after the hydration reaction generates a porous gel, the modified polymer can absorb water and block the pores, increasing the tortuosity of the internal channel, reducing the seepage channel, and improving the anti-seepage and gas barrier properties;
[0043] Low-carbon industrial solid waste gelled powder has hydration activity and can react with water. The hydration products are interwoven to form a solid network structure, forming a hardened gel, which gives the curing agent good mechanical properties and durability. Through grinding treatment, the specific surface area and activity of the gelled powder are increased, making its hydration reaction more complete and improving the strength of the curing agent.
[0044] The performance index test of a new type of high-efficiency environmentally friendly curing agent obtained in Example 1 of the present application is shown in Table 1:
[0045]
[0046] Table 1
[0047] In order to verify the difference between its performance and that of P.O42.5 cement used alone, the mass parts selected in this embodiment are: low-carbon industrial solid waste gelled powder: 40 parts; silicate cement: 15 parts; sulphoaluminate cement: 12 parts; fly ash: 9 parts; mineral powder: 15 parts; redispersible latex powder: 0.3 parts; polyvinyl alcohol: 0.2 parts; cellulose ether: 0.25 parts; xanthan gum: 0.25 parts; desulfurized dihydrate gypsum: 7 parts; grinding aid 0.1 parts; cement early strength agent 0.5 parts; water reducer powder 0.015 parts; cement accelerator curing agent 0.8 parts;
[0048] The basic performance indicators of the experimental P.O42.5 are shown in Table 2;
[0049]
[0050] Table 2
[0051] The performance indicators of the new environmentally friendly curing agent used in the experiment are shown in Table 3;
[0052]
[0053] Table 3
[0054] The performance comparison between P.O42.5 and the new environmentally friendly curing agent is shown in Table 4 and Table 5;
[0055]
[0056] Table 4
[0057]
[0058] Table 5
[0059] This application has been tested and used in many actual projects, such as the anti-seepage wall of a reservoir;
[0060] Project requirements: TRD mixing piles, horizontal grouting, an anti-seepage wall (40 meters underground, 0.6 meters wide and 6 meters long), 28-day core drilling strength above 0.8MPa. The current design solidification material uses 25%P.O42.5 cement, and the project quality assurance period is 50 years.
[0061] In-situ solidification and trenching are adopted. The current design uses cement as the curing agent. There is water below 1 meter in the local soil layer, and the underground temperature (check the topography) is 11-13℃. The cement test piles below 17 meters are not formed and the strength is not enough to reach 0.8MPa.
[0062] The curing agent material is an environmentally friendly new curing agent. The strength of P.042.5 cement with a 16% content is higher than that with a 25% content. The 40-meter core sampling molding effect is good; the curing depth is 40 meters; after curing treatment, the 28-day core sample is ≥0.8Mpa;
[0063] Example 2: The above example increases the curing strength of the curing agent by using low-carbon industrial solid waste gelled powder, which is further improved on the basis of Example 1 to further increase the curing strength.
[0064] The low-carbon industrial solid waste gel powder also contains 0.5-1.5 parts of wood cellulose and 0.1-0.3 parts of nano silicon carbide.
[0065] The length of wood cellulose is 20-50 μm; the diameter is 1-10 μm; the particle size of nano silicon carbide is 100-200 nm; and it is ground together with other ingredients to form a specific surface area of 900-1000 cm 2 / g of high-activity gelling material.
[0066] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0067] By adding cellulose, the dispersibility and workability of the gelling powder are improved, making the curing agent easier to mix and evenly distribute during preparation and use. Cellulose has strong water absorption and contains a large number of hydroxyl groups (-OH) on its molecular chain. These hydroxyl groups can form hydrogen bonds with water molecules, so that water molecules are adsorbed on the cellulose molecular chain. This characteristic greatly promotes the contact between cement and other gelling materials and water, and accelerates the initial stage of the hydration reaction. In addition, cellulose can effectively increase the interfacial bonding force between organic materials and inorganic materials, effectively retain water and inhibit cracking.
[0068] Nano-SiC has high strength and rigidity, and its surface has catalytic activity. In the hydration reaction, nano-SiC acts as a nucleation site to promote the crystallization and growth of hydration products. In addition, the tiny size and high specific surface area of nano-SiC increase its contact area with cementitious materials such as cement, accelerating the hydration reaction.
[0069] Nano silicon carbide has high hardness, high strength and high elastic modulus. As a reinforcement, it significantly improves the mechanical properties of the curing agent. Nano silicon carbide has good wear resistance and corrosion resistance, which can effectively improve the wear and corrosion resistance of the curing agent, making it more suitable for harsh environments. The tiny particles of nano silicon carbide can fill the pores and cracks in the curing agent, forming a dense physical barrier to prevent the salt in the seawater from penetrating into the interior of the curing agent, thereby protecting the curing agent from salt corrosion. It has high-temperature antioxidant properties and can improve the thermal stability of the curing agent, so that it can still maintain good performance in high temperature environments. A good interface is formed between nano silicon carbide and the curing agent matrix, which can transmit stress and prevent the expansion of cracks, thereby improving the toughness and durability of the curing agent.
[0070] As a part of industrial solid waste, the utilization of nano-silicon carbide further promotes the resource utilization of industrial waste, which is beneficial to environmental protection and sustainable development. Nano-silicon carbide plays a filling and bridging role in the curing agent, which can refine the microstructure of the curing agent and improve its density and uniformity. The surface of nano-silicon carbide has abundant active sites, which can catalyze chemical reactions in the curing agent and promote the generation of hydration products and the hardening process.
[0071] The performance test of the curing agent in Example 2 is shown in Table 6. The mass parts of other components are: low-carbon industrial solid waste gel powder: 40 parts; silicate cement: 15 parts; sulphoaluminate cement: 12 parts; fly ash: 9 parts; mineral powder: 15 parts; redispersible latex powder: 0.3 parts; polyvinyl alcohol: 0.2 parts; cellulose ether: 0.25 parts; xanthan gum: 0.25 parts; desulfurized dihydrate gypsum: 7 parts; grinding aid 0.1 parts; cement early strength agent 0.5 parts; water reducer powder 0.015 parts; cement accelerator curing agent 0.8 parts;
[0072]
[0073] Table 6
[0074] Example 3: Example 2 increases the unconfined compressive strength of the curing agent after use and improves the corrosion resistance by adding wood cellulose and nano-silicon carbide to the curing agent. In order to further optimize the curing agent and improve the mechanical strength, further improvements are made on the basis of Example 2.
[0075] Nano-silicon carbide also includes two specifications, including large particles: particle size 300-500nm; small particles: particle size 1-100nm; the mass ratio of large particles to small particles is 1:1.
[0076] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0077] Large-particle nano-silicon carbide, due to its relatively large particle size, is easy to form a macroscopic skeleton structure during the solidification process, which is distributed in the main stress-bearing parts or structural support parts of the solidified body, playing a role of reinforcement and support; at the microscopic level, large-particle nano-silicon carbide will interweave with other cementitious materials to form a relatively stable network structure, providing strength and hardness. Since the surface area of large-particle nano-silicon carbide is relatively small, less cementitious materials are adsorbed on its surface, thereby forming a more obvious granular structure in the solidified body;
[0078] Small particles of nano-SiC can easily fill in the pores between large particles during the solidification process due to their small particle size; or gather on the surface of large particles of nano-SiC and fill in the tiny pores in large particles of nano-SiC, gelling materials and solidified bodies; small particles of nano-SiC can absorb more gelling materials on their surface due to their large specific surface area, thus forming a denser microstructure in the solidified body; and the large specific surface area of small particles can also accelerate the hydration reaction and improve the microstructure.
[0079] The combination of the two can not only form a multi-level structure in the curing agent to improve density and strength; it can also provide an origin for the hydration reaction, so that the hydration reaction occurs more around small particles, and the small particles are more distributed on the surface of large particles or in the gaps they produce, making the large particles the center of the hydration reaction, producing a structural ladder of outer layer gel-middle layer small particles-inner layer large particles, which greatly increases its stability and further improves the pressure bearing capacity after curing.
[0080] Embodiment 4: Embodiment 3 further increases the curing ability through the combination of different particle sizes. In order to expand the scope of application, further improvements are made on the basis of Embodiment 3.
[0081] The mass ratio of large particles: small particles is (1-9): (1-9);
[0082] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0083] Large particles are mostly suitable for application scenarios such as rapid sedimentation and dehydration, high-strength foundation treatment, rapid construction and backfilling;
[0084] When rapid sedimentation of sludge and improved dewatering efficiency are required, a ratio with more large particles is more appropriate. For example, in the fields of sludge dewatering, pond and lake management, large-particle silicon carbide can precipitate quickly to form a natural sedimentation layer, thereby effectively inhibiting the growth of algae and maintaining water clarity. In situations where the bearing capacity and stability of the foundation need to be improved, such as highway subbase settlement and deformation treatment, bridge surface foundation solidification, etc., large-particle materials can provide stronger skeleton support and enhance the overall strength of the solidified body.
[0085] A specific project example: backfilling of fluidized solidified soil in a hospital foundation pit;
[0086] Project requirements: In urban areas, the construction progress is fast, 500-800 cubic meters of backfill per day, pumping method, fluidity 50 meters self-leveling, 1 day for people to walk on, 28 days strength ≥ 0.8MPa;
[0087] Curing agent: environmentally friendly new curing agent, dosage 12%, slotting soil; fluidized soil bulk density 1650-1750kg / m²; mass ratio of large particles: small particles is 9:1;
[0088] After curing, people can go on the ground in 20 hours, the compressive strength is 0.1MPa in 1 day, and the surface bearing capacity is ≥1.0Mpa in 28 days.
[0089] Small particles are mostly suitable for fine filtration and adsorption, ecological restoration and environmental protection, and improving material uniformity and toughness.
[0090] When fine filtration of harmful substances or bacteria in sludge is required, a ratio with more small particles is more appropriate; for example, in the field of water treatment, small particles of silicon carbide can more efficiently adsorb bacteria and other harmful substances and improve the removal rate. In addition, small particles can also be used as high-quality filtration media to provide fine filtration effects for water treatment;
[0091] In projects that require ecological restoration and environmental protection, such as building beautiful rivers after riverbed silt solidification, repairing the bottom and mudflats of rivers and lakes, etc., small particle materials can better combine with organic matter and microorganisms in the silt to promote the recovery of the ecosystem. At the same time, small particle materials also reduce secondary pollution during the solidification process and improve environmental protection effects;
[0092] In situations where the uniformity and toughness of the solidified body need to be improved, such as the foundation filling materials for the construction of roads, bridges, dams and other projects, small particles can better fill the gaps between large particles to form a more dense and uniform structure. This helps to improve the overall performance and durability of the solidified body;
[0093] Specific project example: a temporary road for solidifying the surface of a swamp silt;
[0094] Engineering requirements: Drill core sampling of the silt layer, the depth of the silt layer is about 30 meters, and the temporary road is passable for engineering vehicles (load 70-80 tons); Product technology: Clear the existing ground surface, measure and verify the silt that is higher than the required elevation of the designed plot, dig out the silt that is bulging, and solidify the base soil in situ (strong mixing method). The parameters of the solidification treatment method are as follows:
[0095] The main material is a new environmentally friendly curing agent;
[0096] The curing agent dosage is 10%, and the curing depth is 3 meters; the curing water-cement ratio is 0.7, and the mass ratio of large particles: small particles is 3:7; after curing treatment, the surface foundation bearing capacity is ≥0.5Mpa after 28 days.
[0097] The different particle combinations were tested by using Example 3 and Example 4, and the results are shown in Table 7;
[0098] The other ingredients are selected in parts by weight: 40 parts of low-carbon industrial solid waste gelled powder; 15 parts of silicate cement; 12 parts of sulphoaluminate cement; 9 parts of fly ash; 15 parts of mineral powder; 0.3 parts of redispersible latex powder; 0.2 parts of polyvinyl alcohol; 0.25 parts of cellulose ether; 0.25 parts of xanthan gum; 7 parts of desulfurized dihydrate gypsum; 0.1 parts of grinding aid; 0.5 parts of cement early strength agent; 0.015 parts of water reducing agent powder; 0.8 parts of cement accelerator and curing agent; 1 part of wood cellulose;
[0099]
[0100] Table 7
[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A new type of efficient and environmentally friendly curing agent, characterized in that: Its composition specifically includes the following components in parts by weight: Base material cementitious materials: low-carbon industrial solid waste cementitious powder: 35-45 parts; sulphoaluminate cement: 10-15 parts; silicate cement: 10-20 parts; Fly ash: 8-10 parts; Mineral powder: 10-20 parts; Modified polymer: redispersible latex powder: 0.25-0.35 parts; Polyvinyl alcohol: 0.15-0.25 parts; cellulose ether: 0.2-0.3 parts; Xanthan gum: 0.2-0.3 parts; Setting time regulator: desulfurized dihydrate gypsum: 5-8 parts; Additives: grinding aid 0.1-0.15 parts; cement early strength agent 0.5-1 parts; water reducing agent powder 0.015-0.020 parts; cement accelerator and curing agent 0.6-1 parts.
2. A high-efficiency and environmentally friendly new curing agent as claimed in claim 1, characterized in that: The low-carbon industrial solid waste gelled powder is: The industrial solid waste with hydration activity is ground to prepare low carbon active gel powder, specifically: the powder is ground into a specific surface area of 900-1000cm by a grinding aid. 2 / g of high-activity gelling material.
3. A high-efficiency and environmentally friendly new curing agent as claimed in claim 1, characterized in that: The silicate cement uses the new national standard GB175 ordinary silicate cement P.O42.5, with a specific surface area of 360-420m 2 / kg; sulphoaluminate cement is fast-hardening composite sulphoaluminate cement 42.5, with a specific surface area of 360-400m 2 / kg; fly ash is the first-grade ash from power plants; mineral powder is S95 mineral powder.
4. A high-efficiency and environmentally friendly new curing agent as claimed in claim 1, characterized in that: in, The ash content of the redispersible latex powder is 12-18%; the polyvinyl alcohol is PVA2488; the cellulose ether is hydroxypropyl cellulose ether HPMC with a molecular weight of 150,000-200,000; and the molecular weight of the xanthan gum powder is 800,000-1,000,000.
5. A high-efficiency and environmentally friendly new curing agent as claimed in claim 1, characterized in that: The early strength agent is sodium sulfate with a sodium sulfate content greater than 98%; the water reducer is a polycarboxylic acid high-performance water reducer; and the cement coagulation and curing agent is aluminum sulfate.
6. A high-efficiency and environmentally friendly new curing agent as claimed in claim 1, characterized in that: The low-carbon industrial solid waste gelled powder also contains 0.5-1.5 parts of wood cellulose; Nano silicon carbide: 0.1-0.3 parts.
7. A high-efficiency and environmentally friendly new curing agent as claimed in claim 6, characterized in that: The length of wood cellulose is 20-50 μm; the diameter is 1-10 μm; the particle size of nano-silicon carbide is 100-200 nm.
8. A high-efficiency and environmentally friendly new curing agent as claimed in claim 7, characterized in that: Nano-silicon carbide also includes two specifications, including large particles: particle size 300-500nm; small particles: particle size 1-100nm.
9. A high-efficiency and environmentally friendly new curing agent as claimed in claim 1, characterized in that: The mass ratio of large particles: small particles is (1-9): (1-9).
10. A method for preparing the high-efficiency and environmentally friendly new curing agent according to any one of claims 1 to 9, characterized in that: The specific steps are: add the base cementitious material into the dry mixer in sequence, then add the cement early strength agent, stir for 2 minutes, then add the modified polymer, and continue stirring for 3 minutes; then add other additives except the cement early strength agent, continue stirring for 7 minutes, and discharge the material to obtain the curing agent.
Citation Information
Patent Citations
Silt solidification soil construction technology
CN106836186A
Solid-waste-based maritime work repair material and preparation method thereof
CN113511870A
Concrete curing agent and preparation method thereof
CN115707670A
Construction method for reinforcing sludge through polymer modified curing agent
CN117228911A
Stably solidifying composition for viscous soil, or the like
JP2001323265A